Long-term comparative analysis of the main epidemiological indicators for tuberculosis in combination with HIV infection in the Udmurt Republic - E. A. Afanasiev; O. E. Russkikh (Туберкулез и болезни лёгких)
The objective of the study: to assess changes of epidemiological indicators for TB/HIV co-infection in the Udmurt Republic (UR) and the Russian Federation (RF) from 2008 to 2017 and make the prognosis for the next 5 years.Subjects and methods. The main epidemiological indicators for TB/HIV infection were retrospectively analyzed, the data were taken from annual reports of Republican TB Dispensary, Regional Center for AIDS and Infectious Diseases and Federal Research Institute for Health Organization and Informatics by the Russian Ministry of Health.Results. From 2008 to 2017, the incidence of respiratory tuberculosis both in the Russian Federation and in the Udmurt Republic decreased by 43.0%. While the incidence of HIV infection among the population of the Udmurt Republic increased by 148.5%, in the Russian Federation by 79.7%. From 2011 to 2017, the TB/HIV incidence increased in the UR by 76.6%, in the RF by 48.2%. The mortality of tuberculosis patients died of HIV infection increased by 147.6% in the RF, and by 400% in the UR. Trends in forecasts for investigated indicators of TB/HIV co-infection in the Udmurt Republic and the Russian Federation demonstrate their further growth.